2008
DOI: 10.1093/rheumatology/ken356
|View full text |Cite
|
Sign up to set email alerts
|

Variation of immunological response in methotrexate-induced pneumonitis

Abstract: This is the first study to describe the variation of immunological responses in MTX-P with the degree of exposure to MTX. Our findings suggest that MTX-P can be divided into two groups: type 1 MTX-P that occurs early, predominated by neutrophils, lung fibrosis and has a high mortality; and type 2 MTX-P that occurs late, predominated by lymphocytes, has less lung fibrosis and low mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 40 publications
0
33
0
3
Order By: Relevance
“…Several studies have reported that RA-LD is associated with male gender, a history of smoking and seropositivity [1,[12][13][14][15]. Besides, environmental factors [16], drugs [17][18][19], and underlying diseases [4] may also contribute to the occurrence of RA-LD. However, in a few studies, changes in airways have been reported in early RA even in those who have never smoked, independent of seropositivity [9,20].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that RA-LD is associated with male gender, a history of smoking and seropositivity [1,[12][13][14][15]. Besides, environmental factors [16], drugs [17][18][19], and underlying diseases [4] may also contribute to the occurrence of RA-LD. However, in a few studies, changes in airways have been reported in early RA even in those who have never smoked, independent of seropositivity [9,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, these drugs also often have adverse effects. For example, methotrexate is an anti-rheumatic drug that has been reported to increase the risk of interstitial pneumonia [5]. Infliximab, a molecular-targeted drug, was reported to have decreased its effect due to production of neutralizing antibody [4].…”
Section: Discussionmentioning
confidence: 99%
“…Mortality is low. 31 Claire et al compared BAL fluid cell counts of MTXpneumonitis cases with patients on MTX without MTXtoxicity and normal healthy controls. They noted severe lymphocytic alveolitis in MTX-pulmonary toxicity compared with the other two groups.…”
Section: Mechanism Of Pulmonary Toxicitymentioning
confidence: 99%
“…9 Similar case has been reported by Van der Veen et al 35 A recent study from Egypt has reported deterioration of lung function on methotrexate. 31 Masayuki et al studied induction of pulmonary fibrosis by methotrexate in lungs of mice both in vivo and in vitro. They could induce alveolar epithelialecapillary basement membrane changes followed by proliferation and recruitment of myofibroblasts and collagen deposition.…”
Section: Mechanism Of Pulmonary Toxicitymentioning
confidence: 99%